Use of radiative properties to determine temperature and vapours concentration in MAG welding arc (Ar–CO2–Fe plasmas). (6th September 2018) - Wang, Fei; Cressault, Y; Teulet, Ph; Li, Huan; Yang, Ke; Yu, Fusheng
Abstract: This paper introduces a method allowing a fast determination of space- and time-resolved plasma temperature and iron concentration in MAG arcs during the high-current phase. This method consists of measuring the plasma spectral radiation of a 82%Ar–18%CO2 plasma with iron vapours using a high-speed camera filtered by narrow band filters in the spectral intervals of 570–590 nm and 606–627 nm respectively; calculating theoretically the dependence of the absolute emissivity ε 570–590 nm and relative emissivity ε 570–590 nm / ε 607–627 nm versus the plasma temperature and the iron concentration, and comparing the two results in order to deduce the plasma temperature ( T ) and iron concentration ( Y Fe ) fields of the experimental measurements. The evolution of their profile in time and space are coupled to arc recorded images. This method has also been validated for three layers of plasma at the positions of 0.5 mm, 1.5 mm and 2.5 mm above the workpiece by using a high-resolution spectrometer and adopting other existing diagnostics such as Stark broadening. The plasma temperature and iron concentration show good agreement throughout the different methods, which demonstrates the effectiveness of this new method.